Float [videorecording (DVD)] - Bang, Andrea; Amell, Robbie, 1988-; Krusiec, Michelle, 1974- (Lionsgate, 2026)
After her parents' messy divorce, Waverly finds herself yanked from her comfortable life in Alaska to spend the summer in her aunt's sunny beach town.